Institutions and Contributions to Islamic Law in Indonesia’s Legal System - Rokhmad, Abu (Walisongo Law Review (Walrev), 2021)
This research examines the institutionalization, position and contribution of Islamic law to the national legal system. This study uses a qualitative method with a sociological legal approach. The data source comes from legal materials such as laws and other regulations. The research results show that the institutionalization of Islamic law into the national legal system is carried out procedurally, democratically and in accordance with the needs of the community. This institutionalization is a further process and recognition of the position of Islamic law, not only as a raw material for the making of national laws, but also as a source of law (legal sources) and even a source of values (values sources) for the development of national law. The contribution of Islamic law to the development of the national legal system can be seen in the law on marriage, zakat, waqf, hajj, guarantees of halal products and others which substantively do not contradict Islamic law.[]Riset ini mengkaji tentang pelembagaan, posisi dan kontribusi hukum Islam ke dalam sistem hukum nasional. Kajian ini menggunakan metode kualitatif dengan pendekatan sosiologi hukum. Sumber data berasal dari bahan-bahan hukum seperti UU dan regulasi lainnya. Hasil riset menunjukkan bahwa pelembagaan hukum Islam ke dalam sistem hukum nasional dilakukan secara prosedural, demokratis dan sesuai dengan kebutuhan masyarakat. Pelembagaan ini merupakan proses lanjut dan pengakuan mengenai posisi hukum Islam, bukan saja sebagai bahan mentah (raw material) pembuatan hukum nasional, tapi juga sebagai sumber hukum (legal sources) dan bahkan sumber nilai (values sources) pembangunan hukum nasional. Kontribusi hukum Islam dalam pembangunan sistem hukum nasional dapat dilihat pada UU perkawinan, zakat, wakaf, haji, jaminan produk halal dan lainnya yang secara substantif tidak bertentangan dengan hukum Islam.